Combining Fullerenes and Zwitterions in Non‐Conjugated Polymer Interlayers to Raise Solar Cell Efficiency. (3rd July 2018) - Liu, Yao; Sheri, Madhu; Cole, Marcus D.; Emrick, Todd; Russell, Thomas P.
Abstract: Polymer zwitterions were synthesized by nucleophilic ring‐opening of 3, 3′‐(but‐2‐ene‐1, 4‐diyl)bis(1, 2‐oxathiolane 2, 2‐dioxide) (a bis‐sultone) with functional perylene diimide (PDI) or fullerene monomers. Integration of these polymers into solar cell devices as cathode interlayers boosted efficiencies of fullerene‐based organic photovoltaics (OPVs) from 2.75 % to 10.74 %, and of non‐fullerene‐based OPVs from 4.25 % to 10.10 %, demonstrating the versatility of these interlayer materials in OPVs. The fullerene‐containing polymer zwitterion (C60 ‐PZ ) showed a higher interfacial dipole (Δ) value and electron mobility than its PDI counterpart (PDI‐PZ ), affording solar cells with high efficiency. The power ofPDI‐PZ andC60 ‐PZ to improve electron injection and extraction processes when positioned between metal electrodes and organic semiconductors highlights their promise to overcome energy barriers at the hard‐soft materials interface of organic electronics.